Automated feature description of follicle size in assisted reproductive treatment - Sahrim M.; Rahman U.S.A.; Wan Zakiah Wan Ismail; Ismail I.; Balakrishnan S.R.; Juliza Jamaludin (Penerbit UTHM, 2024)
Indexed by WOS/ Scopus